2010
DOI: 10.3354/meps08799
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations in the diet of the mysid Mesopodopsis africana in the St. Lucia Estuary (South Africa)

Abstract: This study presents one of the few known examples where a mysid species has been observed modifying its diet rapidly and under natural conditions in response to environmental changes. Mesopodopsis africana is a dominant mysid in many estuaries along the east coast of South Africa, and a key species in the St. Lucia Estuary, Africa's largest estuarine lake. St. Lucia is currently undergoing severe desiccation owing to freshwater deprivation. Lack of freshwater input has dampened the effect of temporal variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Also, the δ 13 C/δ 15 N bi-plot in our study showed no missing dietary items, which might have been expected had SOM been important in the diet. Other studies have also shown distinct POM and SOM signatures 28,43 . Future studies combining fatty acid analysis and SIA may further disentangle the various sources of organic particulates and their relative importance, including sources found inside lobster burrows (e.g.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Also, the δ 13 C/δ 15 N bi-plot in our study showed no missing dietary items, which might have been expected had SOM been important in the diet. Other studies have also shown distinct POM and SOM signatures 28,43 . Future studies combining fatty acid analysis and SIA may further disentangle the various sources of organic particulates and their relative importance, including sources found inside lobster burrows (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…A final aim was to determine Nephrops' trophic position based on new SIA results from the present study. The SIA data were analysed within a Bayesian framework, an approach which is increasingly used to address ecological problems [27][28][29][30][31][32][33][34] .…”
mentioning
confidence: 99%
“…[23], [24]). Microalgae were then filtered onto previously combusted (450°C, 6 hours) Whatman GF/F filters.…”
Section: Methodsmentioning
confidence: 99%
“…Mysids usually are omnivorous and may feed on cyanobacteria ), benthic algae (Webb et al 1988;Kibirige et al 2003;Carrasco & Perissinotto 2010), phytoplankton (Jerling & Wooldridge 1995;David et al 2006a;Metillo et al 2007;, detritus (Zagursky & Feller 1985;David et al 2006a;Carleton & McKinnon 2007;, microand mesozooplankton, mainly copepods, but also cladocerans, rotifers and meroplankton (Aaser et al 1995;Jerling & Wooldridge 1995;David et al 2006b;Gorokhova & Lehtiniemi 2007;Winkler et al 2007;Barz & Hirche 2009;Carrasco & Perissinotto 2010, benthic invertebrates (harpacticoid copepods; , zooplankton benthic eggs (Viitasalo & Viitasalo 2004;Viitasalo 2007;Karlson & Viitasalo-Frösen 2009;, and mysids from the same or different species (Wittmann 1978;Fenton 1992;Johnston & Ritz 2001).…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…Their wide diet varies seasonally (Viherluoto et al 2000; according to food availability Winkler & Greve 2004;Carrasco & Perissinotto 2010), species (David et al 2006a;Winkler et al 2007;Vilas et al 2008), and ontogenetic stage (Froneman 2001;Gorokhova & Lehtiniemi 2007;Lesutienė et al 2007), with herbivory and carnivory generally being predominant in juveniles and adults, respectively (Branstrator et al 2000;Viherluoto et al 2000). Mysids are suspension-feeders when feeding on detritus or algae (Webb et al 1987), but may change to raptorial feeding when preying on other animals, depending on prey size and swimming behavior (Wooldridge & Webb 1988;).…”
Section: Chapter 1 Introductionmentioning
confidence: 99%